Going Beyond the Dichotomy. Problems of Contemporary Sociology in the Context of the Proposals by Jerzy Łoś - Szalacha-Jarmużek, Joanna; Pietrowicz, Krzysztof (Studia z Historii Filozofii, 2021)
The article attempts to show how certain ideas formulated several decades ago by Jerzy Łoś may be useful from the perspective of contemporary sociology. Starting with a reflection on the relations between philosophy and sociology, the authors of the paper address the problem of the concept of the realisation operator and its utility in formalising the social sciences, taking into account the humanistic coefficient and other elements that constitute a qualitative approach in sociology.